Intensity of Social Media Use and Political Participation of Generation Z In Indonesia: A Correlational Analysis - Stiawan, Agung; Chanthoeurn Dock (International Journal of Geography, Social, and Multicultural Education, 2025)
This study aims to analyze the correlation between the intensity of social media use and political participation among Generation Z in Indonesia. The increasing digital political engagement among youth highlights the need for a quantitative approach to empirically examine this phenomenon. Using a correlational quantitative method, data were collected through an online survey involving 412 Generation Z respondents from various regions in Indonesia. Pearson correlation and simple linear regression were employed as the main analytical techniques, validated by normality, linearity, and homogeneity tests. The findings reveal a positive and significant correlation (r = 0.622; p < 0.05) between the intensity of social media use and the level of political participation. Social media intensity explains 38.7% of the variance in political participation. These results are interpreted through Manuel Castells’ Network Society theory, which explains how digital connectivity shapes new, horizontal modes of political communication. The study contributes theoretically to understanding the transformation of political participation in the networked society and offers practical insights for developing digital political education and youth engagement strategies in the era of digital democracy.